Pegon Arabic Formula Media: Improving Students' Reading Ability - Tabroni, Imam (International Journal of Curriculum Development, Teaching and Learning Innovation, 2023)
Media is one thing that must be considered in a lesson. In learning Arabic, the Arabic pegon formula is a useful medium for improving students' reading skills. Also, the formulation of the problem in this study concerns the use of the Arabic Pegon formula media used at the Daarul U'lum Ta'lim Assembly, is the use of this media able to improve the reading skills of the students? This study aims to determine the effect that occurs on the level of reading proficiency of the majlis ta'lim daarul u'lum students. The research method used in this study is using quantitative research methods with the approach taken in the form of a one group pretest-posttest experiment. From the results of data analysis, it can be concluded that the pegon arabic formula method is able to provide very significant results on the reading proficiency of the students of majlis ta'lim daarul u'lum.